1966
DOI: 10.1126/science.152.3723.783
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Complement: Influence of Sex Hormones on Its Activity

Abstract: Sex hormones influence the hemolytic of one or more of the late-acting components of complement measured in the presence of trisodium ethylenediaminetetraacetate. The titers of the serums of male mice, normally tenfold higher than those of females, fell after castration, becoming about the same as those of females. The titers of the serums from females rose after these mice were castrated, but castration did not affect the activities of the first, second, and fourth components of complement. Serums of normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1966
1966
1989
1989

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The results, summarized in Table XII, show that there was no significant difference in the time of rejection of skin in all four groups of mice. DISCUSSION We have reported that the administration of testosterone or estradiol to mice influences the titer of at least one of the serum complement components which act after the first, second, and fourth components (9). The overall titer of these late-acting components (C'm-EDTA), usually 8-10 times greater in males than in females, increased 1.5-4 times after treatment of mice with testosterone.…”
Section: I' / 6 I Lo5mentioning
confidence: 87%
See 1 more Smart Citation
“…The results, summarized in Table XII, show that there was no significant difference in the time of rejection of skin in all four groups of mice. DISCUSSION We have reported that the administration of testosterone or estradiol to mice influences the titer of at least one of the serum complement components which act after the first, second, and fourth components (9). The overall titer of these late-acting components (C'm-EDTA), usually 8-10 times greater in males than in females, increased 1.5-4 times after treatment of mice with testosterone.…”
Section: I' / 6 I Lo5mentioning
confidence: 87%
“…The study of genetic and hormonal control of complement may lead to a better understanding of the role of complement in a variety of biological processes (6,9,10). Accordingly, we studied the effect of castration and the in vivo effect of exogenous testosterone and estradiol upon mouse complement.…”
mentioning
confidence: 99%
“…The H-2 complex as well as sex hormones influence the levels of several C components in mice (19)(20)(21)(22)(23). Fig.…”
Section: Effects Of H-2 Type and Sex Of Mice On The Levels Of Ss-bpmentioning
confidence: 99%
“…Evidence from animal experimentation also substantiates the concept of a sex difference in susceptibility. Studies have included comparison of resistance and immune response of males and females to various infectious agents (15,20,29,35,36,39), the effects of administering sex hormones (16, 17, 37, 38, [40][41][42][43]47), changes during pregnancy (19,24), and the influence of castration (3,33). Nicol and co-workers (31,32) have emphasized the role of the estrogen hormones, concluding that "our results to date suggest that estrogen is the principal natural stimulant of body defense in both the male and the female .…”
mentioning
confidence: 99%